Gold dinar: the next component in Islamic economics, banking and finance - Meera, Ahamed Kameel Mydin (IIUM Press, 2009)
Islamic banking started with the objective of providing a banking system that conforms to the Shari'h, with the absence of interest or riba. Nonetheless, it has increasingly become evident that a convergence is taking place between the conventional and Islamic banking systems. Indeed, most Islamic financial contracts are now tied to the market interest rate-the very thing they were supposed to avoid. This paper argues that convergence is indeed likely to happen due to arbitrage opportunities between the two systems. This paper reasons that the use of real monies like the gold dinar, like that which existed during the Prophet's time, as necessary for realizing a stable and just Islamic economic and monetary system. Fiat monet, with all its negative socio-economic effects, is simply not compatible with the maqasid al-Shari'ah. This theoretical paper argues in favour of the gold dinar and for its initial application in international trade settlement. It develops a mathematical model, i.e. a none-linear optimization problem to determine an efficient trading matrix that requires the minimum gold to settle the trade balances among participating countries. The solution to the problem also provides each country with a target gold holding for the trading period.